The Embedded Online Pharmacies Web Application - Hiruni J.M.D.K; Weerakoon L.M.R; Jayasinghe S.J.A.S.M.S; Jayarathne P.I.B; D.I De Silva; Dulanji Cooray (International Journal of Engineering and Management Research, 2022)
The embedded online pharmacies system is proposed as a solution for the current medicinal drug shortage in Sri Lanka. With the current economic crisis, there is a serious issue in the society where medicine is lack and the patients do not get them in time. The proposed system consists of two major stakeholders who is the pharmacist and the candidate. It is a platform where all pharmacies are connected locally, and the candidate can search the availability of a particular medication in one go. This system helps in identifying the location of the pharmacy by correctly locating it through google maps. If a particular drug is not available in the online store or if the candidate cannot sort the issue individually, the system provides an option by providing pharmacy help service where a candidate can chat with a pharmacist or upload a prescription in correspondence to the preferred Area of the candidate. This proposed system gives a favorable solution where it connects a candidate to pharmacists around the country and it gives a vast knowledge on the availability of a drug in a particular area in a minimum amount of effort and time. Moreover, this system is a much needed, user-friendly, reliable, and efficient system.